The future of tourism: interview with Peter Bishop about teaching the future - Albert Postma; Peter C. Bishop (Journal of Tourism Futures)
Purpose – As the Journal of Tourism Futures celebrates its tenth anniversary, Dr Albert Postma interviews Dr Peter Bishop, an expert on teaching the future. The interview was held on July 25, 2024. Design/methodology/approach – A personal interview. Findings – The interview provides insights into the importance of teaching the future, the evolution in teaching the future, competencies and skills that the teaching focuses on, challenges of teaching the future in the current era and the role of AI. Originality/value – Bishop shares his expertise on the development of teaching the future, its key features and its challenges in the current era.